Adipokines Pathogenesis in Heart Failure - Fozia Bibi; Ayesha Aslam; Hooria Naseem; Huma Khurshid; Ali Haider; Habiba Ashraf; Saira Rafaqat (Cardiovascular Innovations and Applications)
Many studies have reported that obesity causes heart failure (HF) pathogenesis. The elevated circulating levels of angiopoietin-like protein 2 (ANGPTL2) observed in patients with HF suggest potential links among elevated ANGPTL2 levels, metabolic disturbances, and inflammation. C1q/TNF-related protein 3 and C1q/TNF-related protein 9 are diminished in patients with HF with reduced ejection fraction, in proportion to disease severity, and are associated with elevated morbidity and mortality. In addition, fibroblast growth factor 21 (FGF21) has been suggested to be involved in the pathophysiology of diastolic HF. Further studies are necessary to determine whether FGF21 plays a causal role in HF, and whether measuring circulating FGF21 might effectively improve HF prediction, diagnosis, and prognosis. Osteopontin has also been reported to be upregulated in patients with HF and therefore might potentially serve as a novel prognostic biomarker in patients with chronic HF. A considerable number of patients with community-acquired HF have elevated tumor necrosis factor-alpha, which is associated with significantly diminished survival and significantly elevated risk of HF.